PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA MELALUI EDUKASI VALUE SKILL SKEMA PENCEGAHAN KEKERASAN PEREMPUAN TERHADAP ANAK DI KOTA BANJAR - Mira Andriani; Riza Purnama; Dara Siti Nurjanah; Nova Chalimah Girsang (Universitas Perjuangan Tasikmalaya, 2025)
Initiatives for women's empowerment aim to achieve gender equality across various development sectors and to protect women from violence. Child protection efforts aim to uphold children's rights and safeguard them against various forms of violence, exploitation, discrimination, and other forms of mistreatment. Given the rising number of violence victims, concerted efforts from various stakeholders are required to combat this issue. This community service project aims to empower participants to prevent violence against women and children through an educational program covering eight key skill areas: 1. Moral and character education; 2. Market-trend product innovation; 3. Legal education regarding violence against women and children; 4. Business and family financial management; 5.